Enhancing Security Measures in Edge Computing for Financial Services - Mahesh Prabu Arunachalam (International Journal of Engineering and Management Research, 2024)
Edge computing presents a promising frontier for financial services, offering real-time data processing and reduced latency. However, the decentralized nature of edge networks introduces significant security challenges. This research explores current security vulnerabilities specific to edge computing in financial services and proposes a professional approach to enhance security measures. By integrating robust authentication, encryption protocols, and proactive monitoring strategies, financial institutions can mitigate risks and safeguard sensitive data in edge environments effectively. Yet, the dispersed nature of edge networks presents notable security challenges that demand careful consideration. Edge computing has fundamentally transformed data processing by decentralizing computation closer to the point of data generation, thereby reducing latency and enhancing efficiency across various sectors, including financial services (Shi et al., 2016). However, the widespread adoption of edge devices and decentralized data processing introduce significant security challenges, particularly for financial institutions that manage vast amounts of sensitive data (Yigit et al., 2018). These institutions are prime targets for cyber threats amidst the distributed computing landscape (Aazam et al., 2016). This research aims to tackle these challenges by proposing comprehensive security measures tailored specifically for edge computing environments in the financial sector. Edge computing represents a paradigm shift in how computational tasks are executed, optimizing real-time decision-making and operational efficiency in diverse industries (Shi et al., 2018). Yet, the expanded attack surface of edge networks necessitates robust security frameworks to mitigate risks effectively (Mao et al., 2017). By adopting these measures, financial organizations can uphold the confidentiality, integrity, and availability of sensitive data processed at the edge. This proactive approach not only addresses current security concerns but also establishes a foundation for trust and resilience in the evolving digital landscape of financial services. As edge computing continues to shape the industry, prioritizing robust security frameworks becomes increasingly imperative to safeguarding sensitive financial information and maintaining regulatory compliance.